Differences in mortality in acute coronary syndrome symptom clusters - Riegel, B.; Hanlon, A.; McKinley, S.; Moser, D.; Meischke, H.; Doering, L.; Davidson, Patricia; Pelter, M.; Dracup, K. (Elsevier, 2010)
Background: The timely and accurate identification of symptoms of acute coronary syndrome (ACS) is a challenge forpatients and clinicians. It is unknown whether response times and clinical outcomes differ with specific symptoms. We sought toidentify which ACS symptoms are related 'symptom clusters' and to determine if sample characteristics, response times, and outcomes differ among symptom cluster groups. Methods: In a multisite randomized clinical trial, 3522 patients with known cardiovascular disease were followed up for 2 years. During follow-up, 331 (11%) had a confirmed ACS event. In this group, 8 presenting symptoms were analyzed using cluster analysis. Differences in symptom cluster group characteristics, delay times, and outcomes were examined. Results: The sample was predominately male (67%), older (mean 67.8, S.D. 11.6 years), and white (90%). Four symptom clusters were identified: Classic ACS characterized by chest pain; Pain Symptoms (neck, throat, jaw, back, shoulder, arm pain); Stress Symptoms (shortness of breath, sweating, nausea, indigestion, dread, anxiety); and Diffuse Symptoms, with a low frequency of most symptoms. Those in the Diffuse Symptoms cluster tended to be older (P = .08) and the Pain Symptoms group was most likely to have a history of angina (P = .01). After adjusting for differences, the Diffuse Symptoms cluster demonstrated higher mortality at 2 years (17%) than the other 3 clusters (2%-5%, P b .001), although prehospital delay time did not differ significantly. Conclusion: Most ACS symptoms occur in groups or clusters. Uncharacteristic symptom patterns may delay diagnosis and treatment by clinicians even when patients seek care rapidly. Knowledge of common symptom patterns may facilitate rapid identification of ACS.